INTERNAL AUDIT SYSTEM IN BUDGET ORGANIZATIONS: ENSURING ACCOUNTABILITY AND EFFICIENCY (Journal of Universal Science Research, 2024)
The goals and tasks, principles of internal audit, methods of auditing in accounting departments in budget organizations, and auditable approaches to the control sequence of lims are all taken into consideration in this article, along with the theoretical and practical aspects of internal audit activities in budget organizations and ways of organizing internal audit in budget organizations in an effective manner